2010
DOI: 10.1371/journal.pone.0013800
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Borrelia burgdorferi Response to Environmental Change

Abstract: We examined global changes in protein expression in the B31 strain of Borrelia burgdorferi, in response to two environmental cues (pH and temperature) chosen for their reported similarity to those encountered at different stages of the organism's life cycle. Multidimensional nano-liquid chromatographic separations coupled with tandem mass spectrometry were used to examine the array of proteins (i.e., the proteome) of B. burgdorferi for different pH and temperature culture conditions. Changes in pH and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Using targeted plasmid deletion, the majority of this plasmid has been shown not to be required for viability in the noninfectious strain B31-A; however, a role for lp17 during infectivity or persistence has not been evaluated in an infectious background. Recently, many of the genes on lp17 have been shown to undergo changes in expression under culture conditions that mimic either the tick vector or the mammalian host (1,9,38,42,58). Further studies using mutant strains lacking alternative sigma factors involved in regulating the expression of host-specific genes showed similar alterations in the expression levels of lp17-borne genes (7,11,43,44,49).…”
mentioning
confidence: 99%
“…Using targeted plasmid deletion, the majority of this plasmid has been shown not to be required for viability in the noninfectious strain B31-A; however, a role for lp17 during infectivity or persistence has not been evaluated in an infectious background. Recently, many of the genes on lp17 have been shown to undergo changes in expression under culture conditions that mimic either the tick vector or the mammalian host (1,9,38,42,58). Further studies using mutant strains lacking alternative sigma factors involved in regulating the expression of host-specific genes showed similar alterations in the expression levels of lp17-borne genes (7,11,43,44,49).…”
mentioning
confidence: 99%
“…Previous studies also revealed that bb0405, but not bb0406, is upregulated by temperature and by conditions that mimic the transmission of B. burgdorferi from feeding ticks to the mammalian host (52). Consistent with the notion that the BB0405 and BB0406 proteins are differentially expressed during infection, a recent Borrelia burgdorferi global proteome analysis showed that BB0405 and BB0406 are variably expressed in different environments (53). Data from those previous studies, combined with the observation that BB0406 antibodies develop much later during infection than do BB0405 antibodies, strongly suggest that BB0405 and BB0406 are cotranscribed but not coexpressed during infection.…”
Section: Discussionmentioning
confidence: 53%
“…Information acquired from different culture conditions indicated that systemic adaptations of the proteome occur as B. burgdorferi moves from one environment to another. A significant increase in the abundance of many outer surface exposed proteins (OspC, LA7, P66, P83 and P35 antigens) was observed in this study (10). The aim of our study was to investigate the influence of host tissues on the infection process, especially adherence of pathogenic or non-pathogenic B. burgdorferi, with emphasis on the synthesis of OspA and OspC.…”
Section: Introductionmentioning
confidence: 60%